Aerodynamic optimization of small diffuser Augmented Wind Turbines: A differential evolution approach - Turan Dias Oliveira; Luzia Aparecida Tofaneli; Alex Álisson Bandeira Santos (Energy Conversion and Management: X)
In order to contain the increase in the concentration of CO2 in the atmosphere and its harmful consequences, studies point to the need to increase the participation of non-fossil energy in the world energy matrix. Among the possible alternatives, wind energy has proven to be economically viable and has its growth established in a global scenario. Although a large part of wind generation occurs due to large turbines, small wind turbines meet the demands of distributed and isolated generation. The efficiency of wind turbines, however, is theoretically limited and one possible way to improve the use of wind energy is the use of Diffuser Augmented Wind Turbines (DAWTs). This work aims to study the impact of wind characteristics on the optimal aerodynamic design of a DAWT blade considering non-uniform flow generated using the diffuser. A new expression for the correction of thrust coefficients for high values of axial induction factor is proposed, so that it is suitable for the evaluation of turbines with and without diffusers. Differential Evolution (DE) is used for the evolution of an initial random population of wind turbine rotors to an optimum final population, maximizing energy conversion. The aptitude of each individual to be evolved is evaluated through Blade Element Momentum (BEM) method, using the proposed correction equation. The optimized variables modify the rotor rotation, chord and twist distributions along the turbine radius and pitch angle. The proposed BEM approach, when compared to experimental results for turbines with and without diffusers, showed an average discrepancy of 4.45% for turbines without diffusers and 0.28% for turbines with diffusers, better agreement than other approaches found in the literature. Through the DE optimization it was noted that most of the parameters studied were highly dependent on the wind regime. The use of diffusers in turbines optimized for operation without diffusers allowed for an energy production improvement of up to 28.4% and proved to be dependent on the geometry of the diffuser and the wind regime. A specific optimization process for diffuser operation can lead to energy production improvement up to 32.6% and may affect the benefit of installing the device by up to 22.7%.